1992
DOI: 10.1128/mcb.12.12.5600
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cysteine-rich receptor for fibroblast growth factors.

Abstract: The fibroblast growth factor (FGF) family consists of seven members whose activities are thought to be mediated by multiple receptors. Here we describe the cDNA cloning, expression, and characterization of a cysteine-rich FGF receptor (CFR) that is distinct from previously identified FGF receptors. The deduced amino acid sequence for CFR suggests that it is an integral membrane protein containing a large extracellular domain comprising 16 cysteine-rich repeated units and an intracellular domain of 13 amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 67 publications
(54 reference statements)
1
71
0
Order By: Relevance
“…The PAM-1 receptor was found to be a M r 130,000 integral membrane glycoprotein (15), homologous to cysteine-rich fibroblast growth factor receptor 1 (25). This post-transcriptionally modified receptor is expressed on nearly all epithelial cancers of every type and origin, but not on healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The PAM-1 receptor was found to be a M r 130,000 integral membrane glycoprotein (15), homologous to cysteine-rich fibroblast growth factor receptor 1 (25). This post-transcriptionally modified receptor is expressed on nearly all epithelial cancers of every type and origin, but not on healthy tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the femtomole amount of the protein digest consumed for MALDI analysis, a database search matched 35 peptides to the CFR-1 sequence with a mass accuracy within 50 ppm. These peptides cover 29% of the CFR-1 sequence, thus definitively identifying the protein, which has a calculated molecular weight of approximately 134 kd (Burrus et al, 1992) (Fig. 1b).…”
Section: Purification and Identification Of Antigen 103/51mentioning
confidence: 96%
“…We previously reported that E-selectin ligand-1 (ESL-1) (also referred to as Cysteine-rich fibroblast growth factor receptor, golgi apparatus protein 1, Latent TGF-ÎČ complexed protein-1 or MG160) (15)(16)(17)(18) is an important regulator of TGF-ÎČ maturation in the Golgi apparatus during cartilage homeostasis (19). Loss of ESL-1 in mice led to accelerated TGF-ÎČ maturation and elevated TGF-ÎČ signaling in the growth plate.…”
mentioning
confidence: 99%